Efektivitas Pemberian Daun Dadap Serep Terhadap Penurunan Suhu Tubuh Bayi Post Imunisasi Dpt Di Posyandu Sei Renggas - Puspan Sari, Selvi; Christiani, Meity (Jurnal Masyarakat Indonesia (Jumas), 2023)
Post-immunization, whether in the form of vaccines, injection reactions, pharmacological effects, procedural errors, incidents, or causal relationships that cannot be determined. Unwanted events after immunization that cause babies to have fevers and cause unrest in the community. Research Objective: To determine the effect of giving Dadap Serep leaves on reducing the body temperature of babies after immunization at Posyandu Sei Renggas. Method: This research design uses a One Group Pretest Posttest design where the experimental design is carried out on one group only without a comparison group. The sampling technique used total sampling with a sample size of 20 respondents, data analysis used the Chi Square test. Results: through the Chi-Square Test, a significant value of 0.000 < 0.05 was obtained, so it can be concluded that there is a significant difference in the body temperature of babies post DPT immunization after being treated with samples of dadap serep leaves at posyandu sei renggas in 2022. Conclusion: temperature was obtained The baby's body after DPT immunization before being given the average dadap spare leaf was (1.0000) with a standard deviation (0.000) and after being given the average dadap spare leaf (0.2500) with a standard deviation (0.444). So, the average difference was obtained. -The average body temperature of babies post DPT immunization after and before giving dadap serep leaves decreased by 0.75 degrees Celsius and a significant value of 0.000 <0.05 which shows that there is a significant difference in the body temperature of babies post DPT immunization after being treated with the sample given. dadap spare leaves at Posyandu neighborhoods 3 and 5 Sei Renggas.